Corneal Topographic Changes Due to Pediatric Epiblepharon Surgery - Shindo J; Matsumura N; Nakamura J; Asano M; Ohno T; Mizuki N (Clinical Ophthalmology)
Jun Shindo,1,2 Nozomi Matsumura,1 Jutaro Nakamura,2 Mizuki Asano,1 Tomoko Ohno,1 Nobuhisa Mizuki2 1Department of Ophthalmology, Kanagawa Children’s Medical Center, Yokohama, Kanagawa, 232-8555, Japan; 2Department of Ophthalmology and Visual Science, Yokohama City University Graduate School of Medicine, Yokohama, Kanagawa, 236-0004, JapanCorrespondence: Jun Shindo, Department of Ophthalmology, Kanagawa Children’s Medical Center, Mutsukawa, Yokohama, Kanagawa, 232-8555, Japan, Tel +81 45 711 2351, Fax +81 45 721 3324, Email junjunon.nike.6228@gmail.comPurpose: This study aimed to investigate changes in corneal morphology following pediatric lower-lid epiblepharon surgery using a topographic modeling system 5 (TMS-5®).Patients and Methods: A randomized controlled trial compared two surgical interventions for pediatric epiblepharon: incisional (modified Hotz procedure with lid margin splitting) and nonincisional. Corneal topography analysis using the TMS-5® served as an outcome measure. The study included 89 eyes from 50 children aged 3– 12 years (mean age, 7.5 ± 2.4 years) diagnosed with moderate epiblepharon. Patients were randomly assigned to the incisional (45 eyes from 25 patients) or nonincisional (44 eyes from 25 patients) groups. Parameters including surface regularity index (SRI), Standard Deviation of Corneal Power (SDP), Irregular Astigmatism Index (IAI), and corneal astigmatism (CYL) were evaluated. The positive rate of Keratoconus Screening System (Keratoconus Index [KCI] and Keratoconus Severity Index [KSI]) was assessed.Results: The 6-month postoperative mean changes in corneal astigmatism were − 0.34 ± 0.96 D (p = 0.012) and − 0.21 ± 0.67 D (p = 0.22) in the incisional and nonincisional groups, respectively. Corneal astigmatism parameters significantly improved following both surgical procedures (p < 0.01). Preoperatively, 14.6% and 28.1% of patients were suspected of keratoconus using KCI and KSI, respectively, with a significantly reduced postoperative suspicion positivity rate (p < 0.01).Conclusion: Corneal astigmatism significantly improved in the incisional group. Both surgical methods improved the postoperative corneal surface smoothness, corneal refractive power variability, and irregular astigmatism. Patients with epiblepharon were occasionally suspected of keratoconus when assessed with TMS, with a higher frequency indicated by KSI.Keywords: topographic modeling system, epiblepharon, cornea, keratoconus, astigmatism